KARAKTERISTIK EKSTRAK PEWARNA ALAMI BUGENVIL (Bougainvillea x buttiana“mahara”) PADA PERLAKUAN JENIS PELARUT DAN SUHU EKSTRAKSI - Tanone, Vonny; Wartini, Ni Made; Wrasiati, Luh Putu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 10 No 1 (2023): Scientific Journal of Food Technology (Maret), 2023)
This research aims to determine the effect of solvent types and extraction temperatures on the characteristics of natural dyes of bougainvillea, determine of the solvent type and extraction temperature which can produce natural dyes from bougainvillea with the best characteristics, and identify organic compounds that makeup bougainvillea dye extract from the best treatment. This study used a factorial randomized block design with 2 factors. Factor I is a solvent type consisting of 3 levels: ethanol 96%, ethanol 96%: citric acid 20% (1:1), and citric acid 20%. Factor II is extraction temperature consisting of 3 levels: 30 o C, 45 o C, and 60 o C. The results showed that the treatment of extraction temperature, solvent type, and interaction had an effect on beta cy anin capacity, yield, acidity (pH), brightness (L *), redness (a *), and yellowish level (b *). The treatment of ethanol 96% solvent: citric acid 20% with extraction temperature of 30 o C was the best treatment for obtaining bougainvillea dye extract with characteristics of beta cy anin capacity 413.545 mg/100g, yields of 9,450%, pH 0.835, value of L* 4,335, values of a* 1,740 and value of b* 33,770. O rganic compounds that comprised bougainvillea extract from the best treatment were b etanidin quinone, b etanin, and dicarboxylic derivatives.